2018
DOI: 10.3390/en11040896
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Radiation Transfer Model to Evaluate Performance of Compound Parabolic Concentrator-Based Photovoltaic Systems

Abstract: Abstract:In the past, two-dimensional radiation transfer models (2-D models) were widely used to investigate the optical performance of linear compound parabolic concentrators (CPCs), in which the radiation transfer on the cross-section of CPC troughs is considered. However, the photovoltaic efficiency of solar cells depends on the real incidence angle instead of the projection incidence angle, thus 2-D models can't reasonably evaluate the photovoltaic performance of CPC-based photovoltaic systems (CPVs). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Considering anisotropic light sources, the concentrator factor related to typical MaReCo Solarus [22] structures is roughly 1.4 to 1.5 suns. In the results, this geometry will be considered as a standard geometry and it is schematically represented in Figure 8.…”
Section: Solarus Concentrating Photovoltaic (C-pv) Collectormentioning
confidence: 99%
See 3 more Smart Citations
“…Considering anisotropic light sources, the concentrator factor related to typical MaReCo Solarus [22] structures is roughly 1.4 to 1.5 suns. In the results, this geometry will be considered as a standard geometry and it is schematically represented in Figure 8.…”
Section: Solarus Concentrating Photovoltaic (C-pv) Collectormentioning
confidence: 99%
“…The acceptance angle between both controls the amount of light that can be reflected and finally end up on the receiver. The interesting fact is, only an incident ray that falls in the acceptance angle range will definitely be reflected by both reflectors and reach the receiver [22].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Yousef et al[9] tested a CPV (2.4×) with a polished stainless-steel reflector and found that, as compared to similar solar panels, the electricity from the CPV with and without cooling of solar cells was increased by 52% and 33%, respectively. These works indicated that reflective CPCs can increase the power output, but the increase factor was much less than the geometric concentration due to optical losses resulting from imperfect reflection of the solar rays on their way to the solar cells [10] and electrical losses resulting from higher cell temperatures, inhomogeneous irradiation and increased incidence angles on the solar cells [11][12][13]. The inhomogeneous irradiation on solar cells usually creates hotspots, leading to current mismatch and tending to reduce their power output and durability [14].…”
mentioning
confidence: 99%